Isolation and Diagnosis of Fungi from Samples of Spices in the City of Nasiriya - Iman H. AL.Fayyadh (University of Thi-Qar Journal of Science, 2020)
Examination of (35) samples of spices obtained from local markets for the purposes of isolating and diagnosing fungi growing on them. Anine isolates belonging to 13 different types of fungi were diagnosed by the standard dilution method with three replications, and it has been observed that the most samples from which the fungi were isolated is ginger. It was found that the most isolated species of fungi are Penicillium, Aspergillus, and Rizupes spp. A rare colony of fungi was observed, which indicates contamination of the spices under study with the fungus. The present study aims to identify the potential risks of the presence of fungi in spices and what may result from mycotoxins that may be the cause of many chronic diseases as a result of using these spices in large quantities. The study recommends limiting the use of contaminated spices, especially ginger, in preparing food and its uses, in addition to other types such as cloves, black and white pepper, and other types of spices found in the local markets, especially the expired ones.